การออกแบบและพัฒนาระบบสารสนเทศตราสารหนี้ สำหรับการบริการลูกค้าโดยผ่านเครื่อข่ายอินเตอร์เน็ต - พูนศักดิ์ สามิตติธาดา (จุฬาลงกรณ์มหาวิทยาลัย, 2000)
Analyzes, designs and develops a bond information system for customer services via the Internet. Being capable of presenting bond information for customers and interested people with user friendly tools via the Internet, this information system consists of four categories--1) Business investigation services 2) Bond information services 3) Investment analyzing services 4) General information services. The system design uses services of the main bond system at Dhana Siam Securities Co., Ltd., as a case study starting from collecting requirements for analyzing investments on bonds. The next step is to design methods and procedures of creating importing and exporting information for services, including securities and relational database management system using Microsoft SQL Server 7.0. The system consists of two subsystems. The customer service subsystem helps provide bond information to customers via the Internet developed by Visual Interdev 6.0. The latter is the support subsystem, which creates imports and exports service information from the main bond system developed by Power Builder 6.0. Consequently the study is found to meet the set objective of being able to provide customers information via the Internet. Moreover this research could be an idea for other system development of securities companies